Kooperation und Asymmetrie: Das Entwicklungsprofil eines betrieblichen Ost-West-Projekts; Cooperation and asymmetry: The development profile of an East-West corporate project - Gerlinde Dörr; Tanja Kessel (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2001)
Das vorliegende Papier befaßt sich mit einer transnationalen Unternehmenskooperation. Rekonstruiert wird das Entwicklungsprofil der Kooperation der beiden Automobilhersteller Skoda und Volkswagen, das durch das Ineinandergreifen der beiden aktuellen Tendenzen von Transformation und Globalisierung geprägt ist. Als für den Kooperationserfolg entscheidend zeigte sich nicht nur der von Volkswagen geleistete beträchtliche Know-how- und Managementtransfer an den tschechischen Standort, sondern auch die Art und Weise im Vorgehen. Vor allem das Anschließen an die bestehenden betrieblichen Kompetenzpotentiale erwies sich dabei als Faktor, der der Kooperation die notwendige Tragfähigkeit für den anstehenden großen Lernschritt ermöglicht hat. Die Studie diskutiert die Befunde auf drei Ebenen der Integration: der betrieblichen, der regionalen und der internationalen. Gegenüber der überaus gelungenen internationalen Integration zeigt sich die regionale Integration des Unternehmens als erheblich zurückgeblieben. Mit Blick auf dieses Problem kommen die Autorinnen zu dem Schluß, daß die eingetretene Diskrepanz kein unerwartbares Ergebnis darstellt angesichts der ungleichen Ausstattungen von internationalen Unternehmen und lokaler Industrie und auch nicht vorrangig – wie es sog. Global Player-Strategien vielfach zugeschrieben wird – aus der Tendenz zur Außenorientierung auf das Konzernnetzwerk zu erklären ist. Vielmehr hat sich am Fall gezeigt, daß die begrenzte regionale Integration ganz wesentlich auch ein Ergebnis der Politik ist, die die tschechische Regierung in den wichtigen Anfangsjahren der Transformation verfolgte und die die erforderliche autochthone Restrukturierungsleistung nicht hervorgebracht hat. – – This paper is concerned with a transnational business cooperation. A profile of the development in cooperation is reconstructed, which is shaped by interlocking tendencies of globalisation and transformation. In this regard, the study is part of a larger, more encompassing study of industrial renewal in Eastern Europe, set into motion partially as a result of foreign direct investment from large multinational corporations. The main item of interest is one of the most prominent east-west corporation projects in the transformation countries: the cooperation between the Czech automotive manufacturer Skoda and the German Volkswagen Group. On the basis of numerous samples collected over several years, the central conflicts and strategic turning points in the relationship are examined. The collection of data involves a multilevel analysis – from strategic political to the operative production and management levels – reconstructing the various viewpoints of cooperation partners. Decisive for success provided to be not only Volkswagen's substantial transfer of expertise and management to locations in the Czech Republic, but moreover the manner in which this was performed. Above all, utilization of the existing pool of competency proved to be the factor, which provided stability required for the learning process. Results of the study are discussed with special attention to international and regional integration of transnational corporations. In the case of Skoda, an especially positive development is demonstrated, regarding modernisation, the level of competitiveness, and the competence structure. Entry into western markets on a large scale was successfully achieved. In comparison to this international integration, regional integration remained largely underdeveloped. In looking at this problem, the authors come to the conclusion that the incurred discrepancy was not unexpected, considering the unequal assets of international corporations and local domestic industry. This discrepancy – found in the results – was not caused by the trend of multinationals to orient themselves outwardly (on their own international production network) as often attributed to the so-called global players' strategies. Rather, this case demonstrated that limited regional integration is in large part a result of policies, pursued by the Czech government during the important early transformation years and which failed to result in the necessary national reconstruction effects.
Keywords: 300; Internationale Unternehmenskooperation; Kraftfahrzeugindustrie; Multinationales Unternehmen; Wissenstransfer; Deutsch; Regionale Inzidenz; Tschechische Republik